Binary and ternary solid-liquid phase equilibrium for the systems formed by succinic acid, urea and diethylene glycol: Determination and modelling. (May 2017) - Li, Yanxun; Li, Congcong; Han, Shuo; Zhao, Hongkun
Graphical abstract: Highlights: Solubility of succinic acid in diethylene glycol was determined. Solubility of succinic acid + urea + diethylene glycol was determined. Three ternary phase diagrams were constructed for the ternary system. The ternary phase diagrams were correlated using NRTL model. Abstract: In this work, the solid-liquid phase equilibrium for binary system of succinic acid + diethylene glycol at the temperatures ranging from (298.15 to 333.15) K and ternary system of (succinic acid + urea + diethylene glycol) at 298.15 K, 313.15 K and 333.15 K was built by using the isothermal saturation method under atmospheric pressure (101.2 kPa), and the solubilities were determined by a high-performance liquid chromatography. The solid-phases formed in the ternary system of ((succinic acid + urea + diethylene glycol)) were confirmed by Schreinemaker's method of wet residue, which corresponded to urea, succinic acid, and adduct 2:1 urea-succinic acid (mole ratio). Three isothermal phase diagrams for the ternary system were constructed based on the measured mutual solubility. Each isothermal phase diagram included six crystallization fields, three invariant curves, two invariant points and two co-saturated points. The crystalline region of adduct 2:1 urea-succinic acid is larger than those of the other two solids. The solubility of succinic acid in diethylene glycol was correlated with the modified Apelblat equation, λh equation and NRTL model; and the mutual solubility of the ternary ((succinic acid + urea + diethylene glycol)) system was correlated and calculated by the NRTL model. The interaction parameters' values of succinic acid-urea were acquired. The value of RMSD was 7.11 × 10 −3 for the ternary system. The calculation results had good agreement with the experiment values. Furthermore, the densities of equilibrium liquid phase were acquired. The phase diagrams and the thermodynamic model of the ternary system could provide the basis for design of the adductive crystallization process which was used to separate succinic acid with high purity from dicarboxylic acid mixtures.